Contributory factors and issues towards family planning participation among the men of Banten, Indonesia - Wulandari, Yenie
"Men's participation has major impact on family planning because it can not only ease the responsibilities carried by women in terms of sexual and reproductive health, but it also can accelerate the understanding and implementation of family planning in general. This research uses mix methods research using secondary data from Indonesia's Demographic Health Survey of Banten Province in 2012 as well as informant interviews to explore the factors and issues that contribute towards the participation of men in family planning in Banten. The study shows that social norms and religion appear to be the disabling issues on receiving and applying family planning information since the legacy media have not been pivotal in men's understanding of their role in family planning. It also discovers that religious leaders have a fundamental role in approaching this sensitive and important topic. Because of the patriarchic milieu in Banten, the study proposes a creative communication approach that targets the younger generation."